Mask of the deer woman [large type] - Dove, Laurie L. (Thorndike Press large print diverse voices., 2025)
"Following her daughter's death, detective Carrie Starr has nowhere to go but back to her roots. Starr's father never talked much about the reservation where he was raised, but the tribe needs a new marshal. In the past decade, too many young women have disappeared from the rez. Now local college student Chenoa Cloud is missing. Starr feels lost, and when she catches a glimpse of a figure from her father's stories, with the body of a woman and the antlers of a deer, Starr can't shake the feeling that the spirit is watching her. What she doesn't know is whether Deer Woman is here to guide her or to seek vengeance for the lost daughters Starr can never bring home."--Back cover.